Homeostatic T Cell Proliferation after Islet Transplantation - Paolo Monti; Lorenzo Piemonti (Clinical and Developmental Immunology)
Pancreatic islet transplantation in patients with type 1 diabetes mellitus is performed under immunosuppression to avoid alloreactive T cell responses and to control the reactivation of autoreactive memory T cells. However, lymphopenia associated with immunosuppression and T cell depletion can induce a paradoxical expansion of lymphocyte subsets under the influence of homeostatic proliferation. Homeostatic T cell proliferation is mainly driven by the IL-7/IL-7 receptor axis, a molecular pathway which is not affected by standard immune-suppressive drugs and, consequently, represents a novel potential target for immuno-modulatory strategies. In this review, we will discuss how homeostatic T cell proliferation can support autoimmunity recurrence after islet transplantation and how it can be targeted by new therapeutic approaches.